Macro-meso failure mechanism and strength criterion of frozen weakly cemented sandstone under triaxial unloading - Deng, Qinghai; Fu, Hao; Wang, Junchao; An, Xiaobiao; Lyu, Xianzhou (Frontiers in Earth Science, 2025)
IntroductionIn the excavation engineering of tunnels and mines in the western cold region, the unloading failure zone is mainly caused by stress release. This study aimed to investigate the deformation and failure mechanism of frozen weakly cemented sandstone (FWCS) when the initial principal stress σ3 was 3, 6, or 10 MPa.MethodsA conventional triaxial compression test and a triaxial unloading test with an unloading rate of 0.05 MPa/s were carried out. Based on the experimental data and mathematical analysis methods, the non-linear criterion was constructed and analyzed. The microfracture characteristics of the damaged surface were studied by scanning electron microscopy (SEM).ResultsThe results show that compared with conventional triaxial compression and room temperature triaxial compression tests, the strength and plastic deformation characteristics of FWCS during unloading were significantly weakened, with transverse deformation and volume strain increased, showing obvious dilatancy characteristics. Unloading reduced the cohesion of FWCS, increased the internal friction angle, and increased the risk of rock failure. Macroscopic and microscopic analysis revealed the failure mechanism of FWCS. The unloading stress ratio was introduced to establish relationships. A non-linear criterion based on the Mohr–Coulomb strength criterion was established, with the power function strength criterion being more accurate in describing the failure of FWCS.DiscussionThis study provides valuable insights into the mechanical properties and failure mechanism of FWCS under unloading conditions, which is beneficial for the excavation engineering of tunnels and mines in the western cold region.